Numerical analysis for elastohydrodynamic lubrication contact of rolling elements in trains - Rao, Etienne Jie Xiang (Nanyang Technological University, 2020)
In the ever urbanising of rail technology, there has been an increasing number of new rail manufacturing every day. As more rails are being built every day, we often face new rail challenges. Full Elastohydrodynamic Lubrication (EHL) conditions under which both the elastic displacements of the surface forming the contact and the effects of pressure has on the viscosity of the lubricant must be taken into account. The complexity of EHL problems has led to a variety of specialised numerical approaches to date. Due to the complexity of this problem, knowledge of physical and technical relationship as well as knowledge of the numerical procedures and methods is necessary to perform EHL simulations. This paper developed a numerical model using the commercial software, COMSOL Multiphysics, for solving EHL line contact problems. The software allows simulation techniques more available to a broader audience of tribology society and to allow more focused research on physical relations rather than on numerical procedures. Two methods, i.e., Integral Approach (IA) and Single Domain (SD) approach, of the calculation of the elastic deflection were implemented and compared. It is proved that SD method is more accurate and efficient. The effect of viscosity, velocity and axle load were analysed. The results show that the increase of viscosity and velocity will lead to a decrease in pressure in the centre region of the contact but the increased pressure towards the outer region. Finally, the surface rough effect was investigated using a transient model which can be considered as an extension of the steady-state model. The surface roughness analysis has shown that it would cause drastic changes in pressure distribution.